Solid electrolyte material and battery using the same

By introducing elements such as Ta or Nb and Cl, Br or I into solid electrolyte materials and preparing them in combination with mechanochemical methods, the problems of low lithium ion conductivity and safety hazards are solved, and high lithium ion conductivity and excellent charging and discharge are achieved. Features and enhance the temperature stability and safety of the battery.

CN114503329BActive Publication Date: 2024-12-13PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080069178.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-05
Filing Date
2020-09-28
Publication Date
2024-12-13
Estimated Expiration
2040-09-28

AI Technical Summary

Technical Problem

The existing solid electrolyte materials have low lithium ion conductivity in lithium-ion batteries and have safety risks of hydrogen sulfide gas generation, especially in temperature-changing environments.

Method used

A solid electrolyte material containing Li, M, O, X and F, where M is Ta or Nb and X is Cl, Br or I is prepared by mechanochemical methods to ensure that the material contains a crystalline phase with high lithium ion conductivity. And by adjusting the molar ratio and adding fluorine to improve electrochemical stability, the presence of sulfur is avoided to prevent the formation of hydrogen sulfide.

Benefits of technology

It achieves high lithium ion conductivity and excellent charging and discharging characteristics, ensures the battery to operate stably in a temperature-changing environment, and improves safety by removing sulfur and enhances electrochemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114503329B_ABST
    Figure CN114503329B_ABST
Patent Text Reader

Abstract

The solid electrolyte material disclosed herein comprises Li, M, O, X and F. M is at least one element selected from Ta and Nb. X is at least one element selected from Cl, Br and I.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a solid electrolyte material and a battery using the same. Background Art

[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte material.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-129312 Summary of the invention

[0006] Problems to be solved by the invention

[0007] An object of the present disclosure is to provide a solid electrolyte material having high lithium ion conductivity.

[0008] Means for solving problems

[0009] The solid electrolyte material disclosed herein comprises Li, M, O, X and F, wherein M is at least one element selected from Ta and Nb, and X is at least one element selected from Cl, Br and I.

[0010] Effects of the Invention

[0011] The present disclosure provides a solid electrolyte material having high lithium ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 A cross-sectional view showing a battery 1000 according to a second embodiment.

[0013] Figure 2 A cross-sectional view showing an electrode material 1100 according to a second embodiment.

[0014] Figure 3 A schematic diagram showing a press-forming die 300 used for evaluating the ion conductivity of a solid electrolyte material.

[0015] Figure 4 This is a graph showing X-ray diffraction patterns of the solid electrolyte materials of Examples 1 to 6 and Comparative Examples 1 and 2.

[0016] Figure 5 This is a graph showing the X-ray diffraction patterns of the solid electrolyte materials of Examples 7 to 11.

[0017] Fig. 6A This is a graph showing the results of cyclic voltammetry measurement of the solid electrolyte materials of Examples 1 to 3.

[0018] Figure 6B This is a graph showing the results of cyclic voltammetry measurement of the solid electrolyte material of Example 4.

[0019] Figure 6C This is a graph for explaining the reduction onset voltage obtained from the results of cyclic voltammetry measurement.

[0020] Figure 7 This is a graph showing the initial discharge characteristics of the battery of Example 1. DETAILED DESCRIPTION

[0021] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0022] (First embodiment)

[0023] The solid electrolyte material of the first embodiment contains Li, M, O, X, and F. M is at least one element selected from Nb and Ta. X is at least one element selected from Cl, Br, and I.

[0024] The solid electrolyte material of the first embodiment has high lithium ion conductivity.

[0025] The solid electrolyte material of the first embodiment can be used to obtain a battery having excellent charge and discharge characteristics.

[0026] The solid electrolyte material of the first embodiment can maintain high lithium ion conductivity within the assumed battery operating temperature range (eg, -30°C to 80°C). Therefore, a battery using the solid electrolyte material of the first embodiment can operate stably even in an environment with temperature changes.

[0027] From the viewpoint of safety, it is preferred that the solid electrolyte material of the first embodiment does not contain sulfur. A solid electrolyte material that does not contain sulfur does not generate hydrogen sulfide even when exposed to the atmosphere, and thus has excellent safety. It should be noted that the sulfide solid electrolyte material disclosed in Patent Document 1 can generate hydrogen sulfide when exposed to the atmosphere.

[0028] In order to improve the ionic conductivity of the solid electrolyte material, the solid electrolyte material of the first embodiment may be substantially composed of Li, M, O, X, and F. Here, "the solid electrolyte material of the first embodiment is substantially composed of Li, M, O, X, and F" means that the molar ratio of the total amount of Li, M, O, X, and F relative to the total amount of all elements constituting the solid electrolyte material of the first embodiment is 90% or more. As an example, the molar ratio may also be 95% or more.

[0029] The solid electrolyte material of the first embodiment may be made of only Li, M, O, X, and F in order to improve the ion conductivity of the solid electrolyte material.

[0030] In order to improve the ion conductivity of the solid electrolyte material, in the solid electrolyte material of the first embodiment, X may contain Cl. Preferably, X may also be Cl.

[0031] The solid electrolyte material of the first embodiment may include a first crystal phase having a peak in a first range of diffraction angle 2θ of 13.7° to 14.8° in an X-ray diffraction pattern. For example, the peak may be in a range of 13.7° to 13.96°.

[0032] The first crystal phase has high lithium ion conductivity. The solid electrolyte material of the first embodiment contains the first crystal phase, so that a path for lithium ion diffusion can be easily formed. As a result, the solid electrolyte material of the first embodiment has high lithium ion conductivity.

[0033] The X-ray diffraction pattern of the solid electrolyte material of the first embodiment can be obtained using Cu-Kα line (wavelength and That is, the wavelengths are 0.15405 nm and 0.15444 nm) and are obtained by X-ray diffraction measurement based on the θ-2θ method.

[0034] The diffraction angle of the peak in the X-ray diffraction pattern is defined as the angle at which the mountain-shaped portion having an SN ratio (i.e., the ratio of the signal S to the background noise N) of 3 or more and a half-value width of 10° or less shows the maximum intensity. The half-value width refers to the angle at which the maximum intensity of the X-ray diffraction peak is set to 1. MAX When the intensity becomes I MAX The width is represented by half the value of the difference between the two diffraction angles.

[0035] The solid electrolyte material of the first embodiment may further have a peak derived from the first crystalline phase in the second range of the diffraction angle 2θ of 24.0 to 25.3° in the X-ray diffraction pattern. This peak may also exist in the range of 24.84° to 24.98°, for example. Such a first crystalline phase has a higher lithium ion conductivity. Therefore, the solid electrolyte material containing the first crystalline phase has a higher lithium ion conductivity.

[0036] In the solid electrolyte material of the first embodiment, the molar ratio of F to the total of X and F may be 1% to 50%. The molar ratio of F to the total of X and F is calculated by the mathematical formula: {(amount of F) / (total amount of all elements constituting X+amount of F)}×100. Hereinafter, the molar ratio of F to the total of X and F is described as "molar ratio F / (X+F)".

[0037] The solid electrolyte material of the first embodiment has high electrochemical stability because it contains fluorine. That is, the solid electrolyte material of the first embodiment has high reduction resistance. When the molar ratio F / (X+F) is 1% to 50%, the solid electrolyte material of the first embodiment can maintain high ionic conductivity and improve electrochemical stability. That is, by having a molar ratio F / (X+F) of 1% to 50%, the solid electrolyte material of the first embodiment has both high ionic conductivity and high electrochemical stability.

[0038] In order to further improve the ion conductivity of the solid electrolyte material, in the solid electrolyte material of the first embodiment, the molar ratio F / (X+F) may be 1% to 10%. For example, the molar ratio F / (X+F) may be 1% to 4%.

[0039] In order to further improve the electrochemical stability of the solid electrolyte material, in the solid electrolyte material of the first embodiment, the molar ratio F / (X+F) may be 10% to 50%.

[0040] In order to further improve the ionic conductivity of the solid electrolyte material, the solid electrolyte material of the first embodiment may further include a second crystalline phase different from the first crystalline phase. That is, the solid electrolyte material of the first embodiment may further include a second crystalline phase having a peak at a diffraction angle 2θ different from the peak of the first crystalline phase in the above-mentioned X-ray diffraction pattern. It is believed that when the solid electrolyte material of the first embodiment includes not only the first crystalline phase but also the second crystalline phase, the conduction of lithium ions between the first crystalline phases can be promoted by the second crystalline phase. Therefore, the lithium ion conductivity is further improved.

[0041] The shape of the solid electrolyte material of the first embodiment is not limited. Examples of the shape are needle-shaped, spherical, and ellipsoidal. The solid electrolyte material of the first embodiment may also be particles. The solid electrolyte material of the first embodiment may also be formed in a particle or plate shape.

[0042] In the case where the shape of the solid electrolyte material of the first embodiment is a particle (e.g., spherical), the solid electrolyte material may have a median particle size of 0.1 μm to 100 μm, or may have a median particle size of 0.5 μm to 10 μm. Thus, the solid electrolyte material of the first embodiment and other materials can be well dispersed. The median particle size of the particle refers to the particle size (d50) corresponding to 50% of the volume accumulation in the volume-based particle size distribution. The volume-based particle size distribution can be measured by a laser diffraction measurement device or an image analysis device.

[0043] When the solid electrolyte material of the first embodiment is in the form of particles (eg, spheres), the solid electrolyte material may have a smaller median particle size than the active material. Thus, the solid electrolyte material of the first embodiment and the active material can be well dispersed.

[0044] <Method for producing solid electrolyte material>

[0045] The solid electrolyte material of the first embodiment is produced by the following method.

[0046] The raw material powder is prepared so as to have a target composition. Examples of the raw material powder are oxides, hydroxides, halides or acyl halides.

[0047] As an example, in a solid electrolyte material composed of Li, M, O, X and F, M is Ta, X is Cl, and the molar ratio Li / M, the molar ratio O / (F+X) and the molar ratio F / (F+X) when the raw materials are mixed are 1.0, 0.2 and 0.1 respectively. 2 O 2 、TaCl 5 and TaF 5 With a Li ratio of 1:1.8:0.2 2 O 2 :TaCl 5 :TaF 5 The molar ratios of Li / M, O / (F+X) and F / (F+X) are determined by the selection of the raw material powders.

[0048] The mixture of raw material powders is mechanochemically reacted with each other (by a mechanochemical grinding method) in a mixing device such as a planetary ball mill to obtain a reactant. The reactant can also be fired in a vacuum or in an inert atmosphere. Alternatively, the mixture can be fired in a vacuum or in an inert gas atmosphere to obtain a reactant. By these methods, the solid electrolyte material of the first embodiment is obtained. The inert atmosphere is, for example, an argon atmosphere or a nitrogen atmosphere.

[0049] By firing the solid electrolyte material, a part of M or a part of X may evaporate. As a result, the molar ratio Li / M and the molar ratio O / (F+X) of the obtained solid electrolyte material may become larger than the values ​​calculated from the molar ratio of the prepared raw material powder. Specifically, the molar ratio Li / M may increase by about 20%, and the molar ratio O / (F+X) may increase by about 40% to 75%.

[0050] By selecting the raw material powders, the mixing ratio of the raw material powders, and the reaction conditions, the position of the X-ray diffraction peak in the solid electrolyte material of the first embodiment, that is, the structure of the crystal phase can be adjusted to a target value.

[0051] The composition of the solid electrolyte material can be determined by, for example, ICP emission spectroscopy, ion chromatography, inert gas fusion-infrared absorption, or EPMA (Electron Probe Micro Analyzer) method.

[0052] (Second embodiment)

[0053] Hereinafter, the second embodiment will be described, and matters described in the first embodiment will be appropriately omitted.

[0054] The battery of the second embodiment includes a positive electrode, an electrolyte layer, and a negative electrode. The electrolyte layer is disposed between the positive electrode and the negative electrode. At least one selected from the positive electrode, the electrolyte layer, and the negative electrode contains the solid electrolyte material of the first embodiment.

[0055] The battery of the second embodiment has excellent charge and discharge characteristics.

[0056] Figure 1 A cross-sectional view showing a battery 1000 according to a second embodiment.

[0057] The battery 1000 includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 . The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .

[0058] The positive electrode 201 includes positive electrode active material particles 204 and solid electrolyte particles 100 .

[0059] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material.

[0060] The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100 .

[0061] The solid electrolyte particle 100 is a particle containing the solid electrolyte material of the first embodiment. The solid electrolyte particle 100 may also be a particle containing the solid electrolyte material of the first embodiment as a main component. The so-called "particle containing the solid electrolyte material of the first embodiment as a main component" refers to a particle containing the solid electrolyte material of the first embodiment as the largest component. The solid electrolyte particle 100 may also be a particle made of the solid electrolyte material of the first embodiment.

[0062] The positive electrode 201 contains a material capable of inserting and removing metal ions such as lithium ions. The positive electrode 201 contains, for example, a positive electrode active material (for example, positive electrode active material particles 204 ).

[0063] Examples of positive electrode active materials are lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal oxysulfides or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are Li(NiCoAl)O 2 、Li(NiCoMn)O 2 or LiCoO 2 .

[0064] From the viewpoint of battery cost and safety, lithium phosphate may be used as the positive electrode active material.

[0065] When the positive electrode 201 contains the solid electrolyte material of the first embodiment and X contains I (i.e., iodine), lithium iron phosphate can also be used as the positive electrode active material. The solid electrolyte material of the first embodiment containing I is easily oxidized. If lithium iron phosphate is used as the positive electrode active material, the oxidation reaction of the solid electrolyte material can be suppressed. That is, the formation of an oxide layer with low lithium ion conductivity can be suppressed. As a result, the battery has a high charge and discharge efficiency.

[0066] The positive electrode 201 contains not only the solid electrolyte material of the first embodiment but also a transition metal fluoride oxide as a positive electrode active material. Even if the solid electrolyte material of the first embodiment is fluorinated by the transition metal fluoride, it is not easy to form a resistance layer. As a result, the battery has a high charge and discharge efficiency.

[0067] The transition metal fluoride oxide contains oxygen and fluorine. As an example, the transition metal fluoride oxide may also be composed of the formula Li p Me q O m F nThe represented compound. Herein, Me is at least one element selected from Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, and P, and satisfies the following mathematical formulas: 0.5 ≤ p ≤ 1.5, 0.5 ≤ q ≤ 1.0, 1 ≤ m < 2, and 0 < n ≤ 1. An example of such a transition metal fluoroxide is Li 1.05 (Ni 0.35 Co 0.35 Mn 0.3 ) 0.95 O 1.9 F 0.1 .

[0068] The positive electrode active material particles 204 may also have a median particle diameter of 0.1 μm to 100 μm. When the positive electrode active material particles 204 have a median particle diameter of 0.1 μm or more, in the positive electrode 201, the positive electrode active material particles 204 and the solid electrolyte particles 100 can form a good dispersion state. Thereby, the charge and discharge characteristics of the battery are improved. When the positive electrode active material particles 204 have a median particle diameter of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 is increased. Thereby, the battery can operate at a high output power.

[0069] The positive electrode active material particles 204 may also have a median particle diameter larger than that of the solid electrolyte particles 100. Thereby, the positive electrode active material particles 204 and the solid electrolyte particles 100 can form a good dispersion state.

[0070] From the viewpoints of the energy density and output power of the battery, in the positive electrode 201, the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the solid electrolyte particles 100 may also be 0.30 to 0.95.

[0071] Figure 2 A cross-sectional view showing the electrode material 1100 of the second embodiment. The electrode material 1100 is, for example, included in the positive electrode 201. In order to prevent the electrode active material particles 206 from reacting with the solid electrolyte particles 100, a coating layer 216 may be formed on the surface of the electrode active material particles 206. Thereby, an increase in the reaction overvoltage of the battery can be suppressed. Examples of the coating material contained in the coating layer 216 are sulfide solid electrolytes, oxide solid electrolytes, or halide solid electrolytes.

[0072] When the solid electrolyte particle 100 is a sulfide solid electrolyte, the covering material may be the solid electrolyte material of the first embodiment, and X may be at least one element selected from Cl and Br. Such a solid electrolyte material of the first embodiment is less susceptible to oxidation than a sulfide solid electrolyte. As a result, the increase in the reaction overvoltage of the battery can be suppressed.

[0073] When the solid electrolyte particle 100 is the solid electrolyte material of the first embodiment and X contains I, the covering material may be the solid electrolyte material of the first embodiment and X may be at least one element selected from Cl and Br. The solid electrolyte material of the first embodiment not containing I is less susceptible to oxidation than the solid electrolyte material of the first embodiment containing I. As a result, the battery has high charge and discharge efficiency.

[0074] When the solid electrolyte particle 100 is the solid electrolyte material of the first embodiment and X includes I, the covering material may also include an oxide solid electrolyte. The oxide solid electrolyte may also be lithium niobate which has excellent stability even at high potential. Thus, the battery has high charge and discharge efficiency.

[0075] The positive electrode 201 may also be made of a first positive electrode layer containing a first positive electrode active material and a second positive electrode layer containing a second positive electrode active material. Among them, the second positive electrode layer is arranged between the first positive electrode layer and the electrolyte layer 202, and the first positive electrode layer and the second positive electrode layer contain the solid electrolyte material of the first embodiment containing I, and a covering layer 216 is formed on the surface of the second positive electrode active material. According to the above structure, it is possible to suppress the solid electrolyte material of the first embodiment contained in the electrolyte layer 202 from being oxidized by the second positive electrode active material. As a result, the battery has a high charging capacity. Examples of covering materials contained in the covering layer 216 are sulfide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, or halide solid electrolytes. However, in the case where the covering material is a halide solid electrolyte, I is not contained as a halogen element. The first positive electrode active material may be the same material as the second positive electrode active material, or may be a material different from the second positive electrode active material.

[0076] From the viewpoint of the energy density and output of the battery, the positive electrode 201 may have a thickness of 10 μm to 500 μm.

[0077] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. The electrolyte layer 202 may also be a solid electrolyte layer. The solid electrolyte material contained in the electrolyte layer 202 may also contain the solid electrolyte material of the first embodiment. The solid electrolyte material contained in the electrolyte layer 202 may also be made of only the solid electrolyte material of the first embodiment.

[0078] The solid electrolyte material contained in the electrolyte layer 202 may be composed only of a solid electrolyte material different from the solid electrolyte material of the first embodiment. An example of a solid electrolyte material different from the solid electrolyte material of the first embodiment is Li 2 MgX' 4 , Li 2 FeX' 4 、Li(Al、Ga、In)X' 4 , Li 3 (Al, Ga, In)X' 6 or LiI. Wherein, X' is at least one element selected from F, Cl, Br and I.

[0079] Hereinafter, the solid electrolyte material of the first embodiment is referred to as a first solid electrolyte material. A solid electrolyte material different from the solid electrolyte material of the first embodiment is referred to as a second solid electrolyte material.

[0080] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed.

[0081] The electrolyte layer 202 may have a thickness of 1 μm to 100 μm. When the electrolyte layer 202 has a thickness of 1 μm or more, the positive electrode 201 and the negative electrode 203 are less likely to short-circuit. When the electrolyte layer 202 has a thickness of 100 μm or less, the battery can operate at a high output.

[0082] Another electrolyte layer may be further provided between the electrolyte layer 202 and the negative electrode 203. For example, when the electrolyte layer 202 includes a first solid electrolyte material, in order to more stably maintain the high ion conductivity of the solid electrolyte material, an electrolyte layer composed of another solid electrolyte material that is more electrochemically stable than the solid electrolyte material may be further provided.

[0083] The negative electrode 203 contains a material capable of inserting and removing metal ions (eg, lithium ions). The negative electrode 203 contains, for example, a negative electrode active material (eg, negative electrode active material particles 205).

[0084] Examples of negative electrode active materials are metal materials, carbon materials, oxides, nitrides, tin compounds or silicon compounds. The metal material may be a single metal or an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials are natural graphite, coke, graphitized carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon. From the viewpoint of capacity density, preferred examples of negative electrode active materials are silicon (i.e., Si), tin (i.e., Sn), silicon compounds or tin compounds.

[0085] The negative electrode active material can also be selected based on the reduction resistance of the solid electrolyte material contained in the negative electrode 203. In the case where the negative electrode 203 contains the first solid electrolyte material, a material that can insert and extract lithium ions at a voltage of 0.27V or more relative to lithium can also be used as the negative electrode active material. If the negative electrode active material is such a material, it is possible to suppress the first solid electrolyte material contained in the negative electrode 203 from being reduced. As a result, the battery has a high charge and discharge efficiency. Examples of the material are titanium oxide, indium metal, or lithium alloy. Examples of titanium oxide are Li 4 Ti 5 O 12 、LiTi 2 O 4 or TiO 2 .

[0086] The negative electrode active material particles 205 may also have a median particle size of 0.1 μm to 100 μm. When the negative electrode active material particles 205 have a median particle size of 0.1 μm or more, the negative electrode active material particles 205 and the solid electrolyte particles 100 can form a good dispersion state in the negative electrode 203. As a result, the charge and discharge characteristics of the battery are improved. When the negative electrode active material particles 205 have a median particle size of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 is increased. As a result, the battery can operate at a high output power.

[0087] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. In this way, the negative electrode active material particles 205 and the solid electrolyte particles 100 can be in a well-dispersed state.

[0088] From the viewpoint of battery energy density and output, in the negative electrode 203 , the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 to 0.95.

[0089] Figure 2The electrode material 1100 shown in the figure may also be contained in the negative electrode 203. In order to prevent the solid electrolyte particles 100 from reacting with the negative electrode active material (i.e., the electrode active material particles 206), a covering layer 216 may also be formed on the surface of the electrode active material particles 206. As a result, the battery has a high charge and discharge efficiency. Examples of the covering material contained in the covering layer 216 are sulfide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, or halide solid electrolytes.

[0090] When the solid electrolyte particles 100 are the first solid electrolyte material, the covering material may be a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer solid electrolyte. An example of a sulfide solid electrolyte is Li 2 SP 2 S 5 An example of an oxide solid electrolyte is trilithium phosphate. An example of a polymer solid electrolyte is a composite compound of polyethylene oxide and a lithium salt. An example of such a polymer solid electrolyte is lithium bis(trifluoromethanesulfonyl)imide.

[0091] From the viewpoint of the energy density and output of the battery, the negative electrode 203 may have a thickness of 10 μm to 500 μm.

[0092] For the purpose of improving ion conductivity, at least one selected from the positive electrode 201, the electrolyte layer 202 and the negative electrode 203 may contain a second solid electrolyte material. Examples of the second solid electrolyte material are sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes or organic polymer solid electrolytes.

[0093] In the present disclosure, "sulfide solid electrolyte" refers to a solid electrolyte containing sulfur. "Oxide solid electrolyte" refers to a solid electrolyte containing oxygen. Oxide solid electrolytes may also contain anions other than oxygen (however, sulfur anions and halide anions are excluded). "Halide solid electrolyte" refers to a solid electrolyte containing halogen elements and no sulfur. Halide solid electrolytes may contain not only halogen elements but also oxygen.

[0094] An example of a sulfide solid electrolyte is Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 SB 2 S 3 , Li 2 S-GeS 2 , Li 3.25 Ge 0.25 P 0.75 S 4or Li 10 G 2 S 12 .

[0095] Examples of oxide solid electrolytes are:

[0096] (i)LiTi 2 (PO 4 ) 3 or NASICON type solid electrolytes such as its element substitution products,

[0097] (ii) (LaLi)TiO 3 Such perovskite solid electrolytes,

[0098] (iii)Li 14 ZnGe 4 O 16 , Li 4 SiO 4 、LiGeO 4 or LISICON type solid electrolytes such as its element substitution products,

[0099] (iv)Li 7 La 3 Zr 2 O 12 or a garnet-type solid electrolyte such as an element substitution body thereof, or

[0100] (v)Li 3 PO 4 or its N-substituted form.

[0101] An example of a halide solid electrolyte is Li a Me' b Y c Z 6 A compound represented by . Wherein, the mathematical formulas are satisfied: a+mb+3c=6 and c>0. Me' is at least one selected from metal elements and semi-metal elements other than Li and Y. Z is at least one element selected from F, Cl, Br and I. The value of m represents the valence of Me'.

[0102] "Semi-metallic elements" are B, Si, Ge, As, Sb and Te. "Metallic elements" are all elements contained in Groups 1 to 12 of the periodic table (however, excluding hydrogen) and all elements contained in Groups 13 to 16 of the periodic table (however, excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S and Se). Me' may also be at least one element selected from Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta and Nb.

[0103] An example of a halide solid electrolyte is Li 3 YC 6 or Li 3 Yb 6 .

[0104] When the electrolyte layer 202 contains the first solid electrolyte material, the negative electrode 203 may also contain a sulfide solid electrolyte. Thus, the sulfide solid electrolyte, which is electrochemically stable with respect to the negative electrode active material, inhibits the first solid electrolyte material and the negative electrode active material from contacting each other. As a result, the battery has a low internal resistance.

[0105] Examples of organic polymer solid electrolytes are compounds of polymer compounds and lithium salts. The polymer compounds may also have an ethylene oxide structure. The polymer compounds having an ethylene oxide structure can contain a large amount of lithium salts and thus have higher ion conductivity.

[0106] An example of a lithium salt is LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiSO 3 CF 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ) or LiC(SO 2 CF 3 ) 3 One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.

[0107] In order to facilitate the transfer of lithium ions and improve the output characteristics of the battery, at least one selected from the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a non-aqueous electrolyte solution, a gel electrolyte, or an ionic liquid.

[0108] The non-aqueous electrolyte comprises a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents or fluorine solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorine solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate or fluorodimethyl carbonate. One non-aqueous solvent selected from them can also be used alone. Alternatively, a mixture of two or more nonaqueous solvents selected from these may be used.

[0109] An example of a lithium salt is LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiSO 3 CF 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ) or LiC(SO 2 CF 3 ) 3 One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 mol / L to 2 mol / L.

[0110] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte solution can be used. Examples of the polymer material are polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0111] Examples of cations contained in ionic liquids are:

[0112] (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium,

[0113] (ii) an aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium or piperidinium, or

[0114] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.

[0115] An example of an anion contained in an ionic liquid is PF 6 - , BF 4 - , SbF 6 - , AsF 6 - 、SO 3 CF 3 - 、N(SO 2 CF 3 ) 2 - 、N(SO 2 C 2 F 5 ) 2 - 、N(SO 2 CF 3 )(SO 2 C 4 F 9 ) - or C(SO 2 CF 3 ) 3 - .

[0116] The ionic liquid may also contain a lithium salt.

[0117] For the purpose of improving the adhesion between particles, at least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a binder.

[0118] The example of binder is polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene-butadiene rubber or carboxymethyl cellulose. As binder, copolymer can also be used. The example of this binder is a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. A mixture of two or more selected from the above-mentioned materials can also be used.

[0119] For the purpose of improving electron conductivity, at least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent.

[0120] Examples of conductive additives are:

[0121] (i) Graphites such as natural graphite or artificial graphite,

[0122] (ii) Carbon blacks such as acetylene black or Ketjen black,

[0123] (iii) Conductive fibers such as carbon fibers or metal fibers,

[0124] (iv) fluorinated carbon,

[0125] (v) Metal powders such as aluminum,

[0126] (vi) Conductive whiskers such as zinc oxide or potassium titanate,

[0127] (vii) conductive metal oxides such as titanium oxide, or

[0128] (viii) Conductive polymer compounds such as polyaniline, polypyrrole or polythiophene.

[0129] For cost reduction, the conductive auxiliary agent (i) or (ii) mentioned above may be used.

[0130] Examples of the shape of the battery of the second embodiment include a coin type, a cylindrical type, a rectangular type, a sheet type, a button type, a flat type, and a laminate type.

[0131] Example

[0132] Hereinafter, the present disclosure will be described in more detail using examples.

[0133] (Example 1)

[0134] [Production of solid electrolyte materials]

[0135] In a dry atmosphere having a dew point of -30°C or less (hereinafter referred to as "dry atmosphere"), a raw material powder was prepared according to Li 2 O 2 :TaCl 5 :TaF 5 Prepare Li in a manner such that the molar ratio becomes 1:1.9:0.1 2 O 2 、TaCl 5 and TaF 5 . These raw material powders were crushed and mixed in a mortar to obtain a mixed powder. The obtained mixed powder was ground using a planetary ball mill (manufactured by Fritsch, P-7 type) for 24 hours at 600 rpm. Next, the mixed powder was calcined at 200°C for 6 hours. In this way, a powder of the solid electrolyte material of Example 1 containing a crystalline phase made of Li, Ta, O, Cl and F was obtained.

[0136] [Evaluation of ionic conductivity]

[0137] Figure 3 A schematic diagram showing a press-forming die 300 used for evaluating the ion conductivity of a solid electrolyte material.

[0138] The press forming die 300 includes a punch upper portion 301, a frame 302, and a punch lower portion 303. The frame 302 is formed of insulating polycarbonate. The punch upper portion 301 and the punch lower portion 303 are both formed of electronically conductive stainless steel.

[0139] use Figure 3 The press forming die 300 shown in FIG. 1 was used to measure the ionic conductivity of the solid electrolyte material of Example 1 by the following method.

[0140] In a dry atmosphere, the powder of the solid electrolyte material of Example 1 (ie, Figure 3 The powder of the solid electrolyte material 101 is filled in the press-forming die 300. In the press-forming die 300, a pressure of 300 MPa is applied to the solid electrolyte material of Example 1 using the punch upper portion 301.

[0141] Under the state of applying pressure, the punch upper part 301 and the punch lower part 303 are connected to a constant potential meter (VersaSTAT4 of Princeton Applied Research) equipped with a frequency response analyzer. The punch upper part 301 is connected to the working electrode and the potential measurement terminal. The punch lower part 303 is connected to the counter electrode and the reference electrode. The ionic conductivity of the solid electrolyte material of Example 1 was measured at room temperature by electrochemical impedance spectroscopy. As a result, the ionic conductivity measured at 22°C was 7.7mS / cm.

[0142] [X-ray diffraction]

[0143] Figure 4 This is a graph showing an X-ray diffraction pattern of the solid electrolyte material of Example 1. Figure 4 The results shown in were determined by the following method.

[0144] The X-ray diffraction pattern of the solid electrolyte material of Example 1 was measured using an X-ray diffraction device (Rigaku Co., Ltd., MiniFlex600) in a dry atmosphere with a dew point of -45°C or less. As an X-ray source, Cu-Kα rays (wavelength and ).

[0145] The solid electrolyte material of Example 1 has diffraction peaks at 13.70° (i.e., the first range) and 25.30° (i.e., the second range). Therefore, the solid electrolyte material of Example 1 contains the first crystal phase having high lithium ion conductivity.

[0146] The solid electrolyte material of Example 1 also has a diffraction peak derived from LiCl. Therefore, the solid electrolyte material of Example 1 also contains a second crystal phase.

[0147] [Evaluation of reduction resistance]

[0148] The reduction resistance of the solid electrolyte material is evaluated by the reduction reaction start voltage of the solid electrolyte material (hereinafter referred to as “reduction start voltage”). The reduction start voltage of the solid electrolyte material is obtained by cyclic voltammetry measurement (hereinafter referred to as CV measurement).

[0149] Fig. 6A This is a graph showing the results of CV measurement of the solid electrolyte material of Example 1. Fig. 6A The results shown in were determined by the following method.

[0150] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material of Example 1 (120 mg, thickness: 500 μm) and the sulfide solid electrolyte (50 mg) were stacked in this order to obtain a stacked body. As the sulfide solid electrolyte, Li 2 SP 2 S 5 A pressure of 360 MPa was applied to the stacked body to form a solid electrolyte layer.

[0151] Next, Li metal (thickness: 300 μm) was stacked on the solid electrolyte layer formed of the sulfide solid electrolyte, and a pressure of 80 MPa was applied to the stacked body.

[0152] Next, current collectors made of stainless steel were placed above and below the stacked body, and current collecting leads were attached to the current collectors.

[0153] In this manner, the CV measurement cell of Example 1 was obtained.

[0154] The obtained CV measurement cell was placed in a thermostatic chamber at 25°C. For Li, a voltage was applied at a scanning voltage rate of -2 mV / sec from the open circuit voltage (OCV) to 0.5 V. If the solid electrolyte material is reduced, a current accompanying the reduction reaction is observed. The reduction start voltage is defined as the current amount at which the OCV is set to I 0 The current I x Become I 0 It should be noted that, in the case of the above-mentioned measurement method, the current value becomes a negative value. Figure 6C This is a graph for explaining the reduction onset voltage obtained from the results of CV measurement.

[0155] In the solid electrolyte material of Example 1, I 0 3.0×10 -7 A, the reduction starting voltage is 2.3V.

[0156] [Battery production]

[0157] In an argon atmosphere having a dew point of -60°C or less, the solid electrolyte material of Example 1 and LiCoO as a positive electrode active material were prepared at a volume ratio of 50:50. 2 These materials were mixed in a mortar to obtain a positive electrode mixture.

[0158] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material of Example 1 (120 mg, thickness: 500 μm) and the above-mentioned positive electrode mixture (10.6 mg) were stacked in order to obtain a stack. A pressure of 360 MPa was applied to the stack to form a solid electrolyte layer and a first electrode.

[0159] Next, a Li-In alloy having a thickness of 200 μm was stacked on the solid electrolyte layer, and a pressure of 80 MPa was applied to the stacked body to form a second electrode.

[0160] The first electrode is a positive electrode, and the second electrode is a negative electrode.

[0161] A current collector made of stainless steel is attached to the first electrode and the second electrode, and a current collecting lead is attached to the current collector.

[0162] Finally, an insulating ferrule is used to block the inside of the insulating tube from the outside atmosphere, thereby sealing the inside of the tube.

[0163] In this manner, the battery of Example 1 was obtained.

[0164] [Charge and discharge test]

[0165] Figure 7 This is a graph showing the initial discharge characteristics of the battery of Example 1. Figure 7 The results shown in were determined by the following method.

[0166] The battery of Example 1 was placed in a thermostatic chamber at 25°C. The battery of Example 1 was charged at a current value of 56 μA until the voltage reached 3.6 V. This current density was equivalent to a 0.05C rate. Next, the battery was discharged at a current value of 56 μA until the voltage reached 2.5 V. The battery of Example 1 was charged and discharged at room temperature.

[0167] As a result of the charge and discharge test, the battery of Example 1 had an initial discharge capacity of 0.80 mAh.

[0168] (Examples 2 to 6)

[0169] [Production of solid electrolyte materials]

[0170] In Example 2, as raw material powder, according to Li 2 O 2 :TaCl 5 :TaF 5 Li was prepared in such a way that the molar ratio became 1:1.8:0.2 2 O 2 、TaCl 5 and TaF 5 .

[0171] In Example 3, as raw material powder, according to Li 2 O 2 :TaCl 5 :TaF 5Li was prepared in a manner such that the molar ratio was 1:1:1. 2 O 2 、TaCl 5 and TaF 5 .

[0172] In Example 4, as raw material powder, according to Li 2 O 2 :NbCl 5 :NbF 5 Li was prepared in such a way that the molar ratio became 1:1.9:0.1 2 O 2 、NbCl 5 and NbF 5 .

[0173] In Example 5, as the raw material powder, according to Li 2 O 2 :NbCl 5 :NbF 5 Li was prepared in such a way that the molar ratio became 1:1.8:0.2 2 O 2 、NbCl 5 and NbF 5 .

[0174] In Example 6, as raw material powder, according to Li 2 O 2 :NbCl 5 :NbF 5 Li was prepared in a manner such that the molar ratio was 1:1:1. 2 O 2 、NbCl 5 and NbF 5 .

[0175] Solid electrolyte materials of Examples 2 to 6 were obtained in the same manner as in Example 1 except for the above-mentioned matters.

[0176] (Example 7)

[0177] In a dry atmosphere having a dew point of -30°C or less (hereinafter referred to as "dry atmosphere"), a raw material powder was prepared according to Li 2 O 2 :TaCl 5 :TaF 5 Li was prepared in such a way that the molar ratio became 1:1.98:0.02 2 O 2 、TaCl 5 and TaF 5. These raw material powders were mixed in a mortar to obtain a mixed powder. The obtained mixed powder was sealed in a container made of quartz glass filled with argon gas and sintered at 350° C. for 6 hours. In this way, a powder of the solid electrolyte material of Example 7 containing a crystalline phase made of Li, Ta, O, Cl and F was obtained.

[0178] (Examples 8 to 11)

[0179] In Example 8, as raw material powder, according to Li 2 O 2 :TaCl 5 :TaF 5 Li was prepared in such a way that the molar ratio became 1:1.96:0.04. 2 O 2 、TaCl 5 and TaF 5 .

[0180] In Example 9, as the raw material powder, according to Li 2 O 2 :TaCl 5 :TaF 5 Li was prepared in such a way that the molar ratio became 1:1.94:0.06 2 O 2 、TaCl 5 and TaF 5 .

[0181] In Example 10, as the raw material powder, according to Li 2 O 2 :TaCl 5 :TaF 5 Li was prepared in such a way that the molar ratio became 1:1.92:0.08 2 O 2 、TaCl 5 and TaF 5 .

[0182] In Example 11, as the raw material powder, according to Li 2 O 2 :TaCl 5 :NbCl 5 :TaF 5 Li was prepared in such a way that the molar ratio became 1:0.92:1:0.08 2 O 2 、TaCl 5 、NbCl 5 and TaF 5 .

[0183] Solid electrolyte materials of Examples 8 to 11 were obtained in the same manner as in Example 1 except for the above-mentioned matters.

[0184] (Comparative Examples 1 and 2)

[0185] In Comparative Example 1, as the raw material powder, LiCl:Li 2 O 2 LiCl and LiF were prepared so that the molar ratio was 0.9:1:0.1. 2 O 2 And LiF.

[0186] In Comparative Example 2, as raw material powder, LiCl:TaCl 5 LiCl and TaCl were prepared so that the molar ratio of LiF was 0.4:1:0.6. 5 And LiF.

[0187] Solid electrolyte materials of Comparative Examples 1 and 2 were obtained in the same manner as in Example 1 except for the above-mentioned matters.

[0188] [Evaluation of ionic conductivity]

[0189] The ion conductivity of the solid electrolyte materials of Examples 2 to 11 and Comparative Examples 1 and 2 was measured in the same manner as in Example 1. Tables 1 and 2 show the measurement results.

[0190] [X-ray diffraction]

[0191] The X-ray diffraction patterns of the solid electrolyte materials of Examples 2 to 11 and Comparative Examples 1 to 2 were measured in the same manner as in Example 1. The measurement results are shown in Figure 4 and 5 middle.

[0192] The solid electrolyte material of Example 2 has diffraction peaks at 13.74° (i.e., the first range) and 24.52° (i.e., the second range). Furthermore, a diffraction peak derived from LiCl is also observed.

[0193] The solid electrolyte material of Example 3 does not have diffraction peaks in the first range and the second range.

[0194] The solid electrolyte material of Example 4 has diffraction peaks at 13.86° (i.e., the first range) and 24.55° (i.e., the second range). Furthermore, a diffraction peak derived from LiCl is also observed.

[0195] The solid electrolyte material of Example 5 has diffraction peaks at 13.96° (i.e., the first range) and 24.56° (i.e., the second range). Furthermore, a diffraction peak derived from LiCl is also observed.

[0196] The solid electrolyte material of Example 6 has diffraction peaks at 14.79° (ie, the first range) and 24.02° (ie, the second range).

[0197] The solid electrolyte material of Example 7 has diffraction peaks at 13.84° (i.e., the first range) and 24.90° (i.e., the second range), and further has a diffraction peak derived from LiCl.

[0198] The solid electrolyte material of Example 8 has diffraction peaks at 13.83° (i.e., the first range) and 24.89° (i.e., the second range). Furthermore, a diffraction peak derived from LiCl is also observed.

[0199] The solid electrolyte material of Example 9 has diffraction peaks at 13.88° (i.e., the first range) and 24.93° (i.e., the second range). Furthermore, a diffraction peak derived from LiCl is also observed.

[0200] The solid electrolyte material of Example 10 has diffraction peaks at 13.84° (i.e., the first range) and 24.89° (i.e., the second range). Furthermore, a diffraction peak derived from LiCl is also observed.

[0201] The solid electrolyte material of Example 11 has diffraction peaks at 13.90° (i.e., the first range) and 24.93° (i.e., the second range). Furthermore, a diffraction peak derived from LiCl is also observed.

[0202] Therefore, the solid electrolyte materials of Example 2 and Examples 4 to 11 contain the first crystal phase.

[0203] The solid electrolyte materials of Examples 2, 4, and 5 to 11 further contain a second crystal phase.

[0204] [Evaluation of reduction resistance]

[0205] The solid electrolyte materials of Examples 2 to 4 were subjected to CV measurements in the same manner as in Example 1. The measurement results are shown in FIG. Fig. 6A and 6B And Table 1.

[0206] In Example 2, I 0 3.6×10 -7 A, the reduction starting voltage is 2.2V.

[0207] In Example 3, I 0 2.6×10 -7 A, the reduction starting voltage is 2.0V.

[0208] In Example 4, I 0 5.1×10 -7A, the reduction starting voltage is 2.8V.

[0209] [Table 1]

[0210]

[0211] [Table 2]

[0212]

[0213] (Inspection)

[0214] As shown in Table 1, the solid electrolyte materials of Examples 1 to 11 have a 1×10 -3 High ion conductivity of mS / cm or more. In addition, as shown by the reduction start voltage of the solid electrolyte materials of Examples 1 to 4, the solid electrolyte material containing Li, M, O, X, and F has high electrochemical stability.

[0215] As shown by comparing Examples 1 to 3, as the value of the molar ratio F / (X+F) increases, the reduction start voltage decreases. That is, as the value of the molar ratio F / (X+F) increases, the electrochemical stability of the solid electrolyte material increases.

[0216] As shown by comparing Examples 1, 2, and 7 to 10 with Example 3, if the molar ratio F / (X+F) is 1% to 10%, the ion conductivity of the solid electrolyte material becomes higher.

[0217] As shown by comparing Examples 2 and 3 with Example 1, if the molar ratio F / (X+F) is 10% to 50%, the electrochemical stability of the solid electrolyte material becomes higher.

[0218] Since the solid electrolyte materials of Examples 1 to 11 do not contain sulfur, they do not generate hydrogen sulfide.

[0219] As described above, the solid electrolyte material of the present disclosure has high lithium ion conductivity and is therefore suitable for providing a battery having excellent charge and discharge characteristics.

[0220] Industrial Applicability

[0221] The battery disclosed herein is used, for example, in an all-solid lithium ion secondary battery.

[0222] Explanation of symbols

[0223] 100 Solid Electrolyte Particles

[0224] 101 Powder of solid electrolyte material

[0225] 201 Positive electrode

[0226] 202 electrolyte layer

[0227] 203 Negative electrode

[0228] 204 Positive electrode active material particles

[0229] 205 Negative electrode active material particles

[0230] 206 Electrode active material particles

[0231] 216 Overlay

[0232] 300 Pressurized Forming Die

[0233] 301 Punch upper part

[0234] 302 frame type

[0235] 303 punch lower part

[0236] 1000 Batteries

[0237] 1100 Electrode Materials

Claims

1. A solid electrolyte material comprising Li, M, O, X and F, in, M is at least one element selected from Ta and Nb, X is at least one element selected from Cl, Br and I, The solid electrolyte material includes a first crystal phase having a peak in a first range of a diffraction angle 2θ of 13.7° to 14.8° in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu—Kα rays.

2. The solid electrolyte material according to claim 1, wherein X contains Cl.

3. The solid electrolyte material according to claim 2, wherein In the X-ray diffraction pattern, a peak derived from the first crystal phase further exists in a second range of values ​​of a diffraction angle 2θ of 24.0° to 25.3°.

4. The solid electrolyte material according to any one of claims 1 to 3, wherein The molar ratio of F to the total of X and F is 1% to 50%.

5. The solid electrolyte material according to claim 4, wherein The molar ratio is 1% to 10%.

6. The solid electrolyte material according to claim 4, wherein The molar ratio is 10% to 50%. 7 . The solid electrolyte material according to claim 1 , further comprising a second crystal phase different from the first crystal phase.

8. A battery comprising: positive electrode, Negative electrode, and An electrolyte layer disposed between the positive electrode and the negative electrode, At least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 7.